Design of Water Monitoring System in Aquaponics Based on Arduino Nano and Raspberry Pi - Prasetya, Nyoman Wira; Imansyah Harahap, Arya Rizky; Aulady, Fadhli; Wulandari, Inayah (Department of Informatics Engineering, 2023)
The aquaponic system is an agricultural technology that can provide a lot of results in a limited space by recirculating water and nutrients from the symbiosis created between fish farming and hydroponic plant cultivation. To maximize the nutritional needs of water that will be supplied to plants and maintain good water conditions for fish life, it is necessary to check several parameters that can be measured in water periodically in fishponds in an aquaponic system so that farmers can provide appropriate actions in managing the system. aquaponic farming. Based on this background, a system was designed using the Internet of Things concept that can monitor water conditions in aquaponic fishponds, store water parameter data in a database, then data can be monitored via the Website. The system is designed using the Arduino Nano microcontroller board as a data processor which is equipped with the ESP8266-07 wifi module which is connected via a WiFi Local Area Network (LAN) network and connected to the Raspberry Pi 3 Model B as a gateway to the database using the MQ Telemetry Transport Protocol (MQTT). The water parameters that are measured in the designed system are: water temperature, water turbidity, dissolved solids, dissolved oxygen, and water acidity (pH). The results of the designed system show that this system can run as expected so that it can facilitate monitoring of water in aquaponic farming systems